Model Kampung Arab Santri Bidik Misi Ma‘had Al-Jami’ah: Adopsi dan Adaptasi Kampung Arab Pare Kediri - Muhammad Mas’ud; Urifatun Anis (Alsina : Journal of Arabic Studies, 2020)
This study aims to describe the model and application of the Adopted and adaptive Arab village of the EGYPT Islamic Boarding Course for English and Arabic village at Pare Kediri to the students of Ya Bismillah Ma'had Al-Jami'ah Putri IAIN Salatiga mission. The method used is interactive qualitative covering three activities: data reduction, data presentation, and concluding. Data was obtained through observation, interview, and documentation. The results of this study indicate that; 1) learning is carried out with the lecture model, Al-Liqa ', al-tamsil and al-munaqosyah. 2) application of management functions that are adopted includes planning, organizing, leadership, and controlling. 3) the supporting factors in the model of the Arabic village, the santri aiming for the mission of Ya Bismillah Ma'had Al-Jami'ah Putri IAIN Salatiga, namely; the methods used by the ustadz and ustadzah, the curriculum, the materials and teaching materials, the ustadz or ustadzah competences and the holding of learning evaluations. The inhibiting factors include: there are limitations to learning Arabic language tools. Besides that, the ustadz / ustadzah has not found the right model for improving Arabic learning in these institutions due to the students' different educational backgrounds.